A smartphone game to prevent HIV among young Kenyans: Household dynamics of gameplay in a feasibility study. (August 2019) - Winskell, Kate; Sabben, Gaëlle; Ondeng'e, Ken; Odero, Isdorah; Akelo, Victor; Mudhune, Victor
Objective: mHealth interventions often favour individual-level effects. This is particularly problematic in contexts where social support and shifts in social norms are critical to sustained behaviour change. Mobile digital games represent a promising health education strategy for youth, including in low-resource settings. We sought to better understand the interpersonal and social interactions that can be elicited by digital games for health. Design: We piloted Tumaini, a smartphone game rooted in interactive narrative designed to prevent HIV among young Africans (aged 11–14), in a randomised controlled feasibility study and analysed reports of the household dynamics surrounding gameplay. Following a 16-day intervention period, phone gameplay log files were downloaded, and intervention arm participants ( n  = 30) completed a gameplay experience survey; eight focus group discussions were held, four with intervention arm participants ( n  = 27) and four with their parents ( n  = 22). Setting: This study took place in Kisumu, Kenya, in Spring 2017. Method: Descriptive statistics were computed from survey responses and log files. Focus group transcripts were labelled, analysed thematically and compared demographically using MAXQDA software. Results: Data from log files, surveys and focus groups indicate that the game generated considerable interaction and dialogue with parents, siblings and friends and served as a catalyst for children to act as advocates for healthful decisions about sex, both within the family and beyond. The game showed a high level of acceptability with parents. Conclusion: Serious digital games using a smartphone platform can generate considerable household interaction. Games can model and facilitate these exchanges, maximising multi-level effects. An additional app for parents could reinforce these effects.